2018
DOI: 10.1108/ijhcqa-12-2016-0181
|View full text |Cite
|
Sign up to set email alerts
|

Data envelopment analysis for estimating efficiency of intensive care units: a case study in Iran

Abstract: Purpose As hospitals are the most costly service providers in every healthcare systems, special attention should be given to their performance in terms of resource allocation and consumption. The purpose of this paper is to evaluate technical, allocative and economic efficiency in intensive care units (ICUs) of hospitals affiliated by Yazd University of Medical Sciences (YUMS) in 2015. Design/methodology/approach This was a descriptive, analytical study conducted in ICUs of seven training hospitals affiliated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Findings indicated that the micro environmental factors affected the quality of services as well as their expenditures. One of the key micro factors is the lengthy waiting time (as indicated in Table 1), impacting the efficiency, effectiveness and customer satisfaction [20][21][22][23]. The results of a meta-analysis by Fazel Hashemi et al showed that this indicator was higher in the emergency departments of Iranian hospitals in comparison with national and international standards.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated that the micro environmental factors affected the quality of services as well as their expenditures. One of the key micro factors is the lengthy waiting time (as indicated in Table 1), impacting the efficiency, effectiveness and customer satisfaction [20][21][22][23]. The results of a meta-analysis by Fazel Hashemi et al showed that this indicator was higher in the emergency departments of Iranian hospitals in comparison with national and international standards.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated that the micro environment factors of public hospitals affected quality of services as well as the expenditures. One of the factors at the micro level was lengthy waiting time, particularly, in emergency rooms (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a case study by WSB (Visa Skola Biznisa) proposed a model that is a product of the joint investment between the the National Louis University. In this model, the key mission of entrepreneurial universities is to help create the opportunity and capacity for local and regional development, to be active in the field of economics and to create a knowledge-based society, as well as to encourage the development of industry, commerce, services, urban development, and technological citizenship in an active and action-oriented form (20,21). Moreover, the results obtained by Etzkowitz showed that the goals of entrepreneurial universities will be realized when the results and achievements of some particular research or innovation are revealed.…”
Section: Fourth Scenario: Alert For Moving Backward To First-generatimentioning
confidence: 99%